1984
DOI: 10.1113/expphysiol.1984.sp002809
|View full text |Cite
|
Sign up to set email alerts
|

Mammary Development and Regression During Lactation in Goats in Relation to Milk Secretion

Abstract: SUMMARYMammary development was assessed in lactating goats using a combination of biopsy (for analysis of nucleic acids) and udder volumes (for determination of gross size). Single biopsies were shown to be highly representative of the composition of the whole gland provided that they were taken from carefully selected sites. Results indicated an increase in both milk yield and the size of the mammary cell population (DNAj) over the first three weeks of lactation.Yield, but not DNAt, continued to increase unti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
105
0
1

Year Published

1986
1986
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(113 citation statements)
references
References 11 publications
7
105
0
1
Order By: Relevance
“…Anderson et al (1981) (Foster, 1977), this difference is not surprising. Anderson et al (1981) also suggested that growth continued during early lactation, an observation later supported by mammary biopsy data (Knight & Peaker, 1984) and now by the present primiparous goat results. Although the peak in parenchyma volume coincided with peak milk yield in some of our goats, the overall results confirm the previous reports that growth ceases after Week 2, several weeks before maximum yield is attained.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Anderson et al (1981) (Foster, 1977), this difference is not surprising. Anderson et al (1981) also suggested that growth continued during early lactation, an observation later supported by mammary biopsy data (Knight & Peaker, 1984) and now by the present primiparous goat results. Although the peak in parenchyma volume coincided with peak milk yield in some of our goats, the overall results confirm the previous reports that growth ceases after Week 2, several weeks before maximum yield is attained.…”
Section: Discussionsupporting
confidence: 67%
“…Simple determinations of gross udder volume by water displacement or plaster cast (Linzell, 1966) took no account of the changes in internal composition. Combining udder volume with tissue biopsy alleviated this problem to some extent (Knight & Peaker, 1984), but only when the biopsy sample could be shown to be representative of the whole gland (essentially late pregnancy and throughout lactation). Taking larger samples (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The average coefficient of lactation persistence was higher than that recommended by Ribeiro (1997) for dairy goats (0.90). The coefficient of lactation persistence has a negative correlation (-0.99), with a declining production rate after peak lactation (c) ( Table 5), which is influenced by the number and activity of the mammary secretory cells (Knight and Peaker, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…However in other reported cases, these activities (or the RNA/DNA ratio) were steady or else augmented up to the 5 th or 6 th month of lactation (Currie, 1972 ;Shirley, 1973 ;Knight and Peaker, 1984). A decrease in mammary DNA level between weeks 3 and 23 was also reported in the goat (Knight and Peaker, 1984 (1976) reported differences in the in vitro metabolic activities of the mammary tissue of 4 hormonally-induced cows for 2 weeks before and one week after milking was begun. These activities reflected differences in milk yield.…”
Section: Introductionmentioning
confidence: 95%
“…Few studies have been done on changes in the metabolic activities of mammary tissue during lactation in cows (Currie, 1972 ;Shirley, 1973 ;Marinez et al, 1976) and goats (Marinez et al, 1976 ;Chilliard et al, 1978 ;Reddy and Ray, 1982 ;Knight and Peaker, 1984 The hormonal treatment given to group I goats (Delouis, 1975) Chilliard (1979Chilliard ( , 1985. The first two enzymes are involved in the de novo synthesis of fatty acids, the third in the hydrolysis and the uptake of circulating triglycerides.…”
Section: Introductionmentioning
confidence: 99%